The Performance of Rice Mower Utilization in Kutai Kartanegara Regency East Kalimantan - Abadi, Farid Rakhmat (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.221, 2017)
ABSTRACT   Rice mower is a cutter machine of rice stem in the harvesting activities. Even though, there are some rice harvesting system which are known with better working performance, this machine can be possibly applied in several region in Indonesia based on the specific location characteristic, due to its lower price and easier operation. The assessment was conducted to understand the performance of rice mower in Kutai Kartanegara Regency, East Kalimantan Province. The experimental design used was completely randomized design with three treatments and five repetitions. Treatments were ordinary rice mower with single operator; while serated sickle; and ordinary sickle as a control using 3 operator in 5x5 m 2 areas. The result was showed that mower machine had the highest field capacity of 0.0290 ha/h; then ordinary sickle by 0.0084 ha/h and serated sickle by 0.0081 ha/h as the lowest. Moreover, yield loss of mower utilization was 0.72% at the lowest; then serated sickle of 0.77% and ordinary sickle of 0.91% in the highest. Mean while, the B/C ratio or mower utilization was lower (1.8) than ordinary and serated sickle utilization which was relatively equal (1.95). Therefore, it can be concluded that mower utilization in stem cutting of the harvesting activity had advantages namely higher capacity and lower yield lost. Keywords : performance, rice mower, Kutai Kartanegara, Kalimantan Timur.